TENNIS ELBOW: ROLE OF LOCAL STEROID INJECTION - Ahmed, Gulzar Saeed; Ali, Muhammad; Trago, Imtiaz Ahmed (Journal of Ayub Medical College Abbottabad, 2012)
Background: Tennis elbow is a condition, characterised by pain and tenderness over the lateral epicondyle of the humerus, and pain on resisted dorsiflexion of the wrist, middle finger, or both. The aim of this randomised controlled trial was to investigate the short term efficacy of local steroid injection compared with oral and topical NSAIDs. Methods: Sixty patients (45 male and 15 female) were included in the study. The mean age was 42 years for men and 40 years for women. They were placed in group A and B (30 cases each). Group A received local steroid injection (triamcinolone 20 mg mixed with lignocaine 2% 1 cc) and topical NSAID cream application (diclofenac diethylammonium) twice a day, tab. diclofenac sodium 50 mg twice a day for 3 weeks. Group B received tab diclofenac 50 mg twice a day and, topical NSAID cream application twice a day for 3 weeks. Assessment of patients was made 3 times; first at the start of the study, 2nd time after 6 weeks, and 3rd time after 12 weeks. A blinded assessor rated the elbow complaints of the patients at resisted dorsiflexion of wrist using VAS (0=no severity, 1-3 mild, 4-6 moderate, 7-9 sever, 10=maximum severity). Results: At six weeks, 22 (73.33%) patient in group A had no pain as compared to 7 (23.33%) patients in group B who were pain free (p<0.0001, Ï‡2=38.75). At 12 weeks 27 (90%) patients in group A were pain free compared to group B in which 7 (23.33%) patients were pain free (p<0.0001, 2Ï‡ =27.56). Conclusion: In patients with tennis elbow, the use of local steroid injection in combination with topical and oral NSAIDs is superior to the use of combination of topical and oral NSAIDs. Better results with combination therapy using local steroid injection may be limited to the short term. Keywords: Tennis elbow, steroid, pain